NEWS ON CRIMINAL LIABILITY FOR OFFENSES RELATED TO DRUGS AND PRODUCTS SUSCEPTIBLE TO HAVING PSYCHOACTIVE EFFECTS, OTHER THAN THOSE PROVIDED FOR BY THE REGULATIONS IN FORCE - Buneci, Bogdan (International Journal of Legal and Social Order, 2025)
Recent reforms in criminal liability for drug and psychoactive substance offenses show a clear trend toward tougher criminal policy, combining repressive measures with rehabilitation and prevention tools. Increased penalties for traffickers, the introduction of aggravating circumstances, and the criminalization of related acts reflect a strategy of reduced tolerance for the phenomenon, while mandatory treatment and psychological counseling programs mark a step toward addressing public health in the context of addiction. However, the intensity and frequency of legislative changes may affect legal certainty and consistency in law enforcement. Repeatedly tightening sanctions and restricting access to alternative measures risks exacerbating prison overcrowding and creating an imbalance between the repressive and rehabilitative aims of the law. A sustainable criminal policy must ensure the proportionality of penalties, the effective implementation of reintegration programs, and the predictability of the regulatory framework in order to maintain confidence in justice and reduce the incidence of crime in the long term.